Eight weeks of core stability training improves landing kinetics for freestyle skiing aerials athletes - Wei, Ming; Fan, Yongzhao; Lu, Zulei; Niu, Xuesong; Wu, Hao (Frontiers in Physiology, 2022)
Freestyle skiing aerials are characterized by technical elements including strength, flexibility and balance. Core stability in freestyle skiing aerials can improve sporting performance. Objective: This study aimed to analyze the effect of eight weeks of core stability training on core stability performance in freestyle skiing aerials. Methods: A randomized controlled study was conducted on 18 aerials athletes. Participants were randomly assigned to a control group (CG; n = 9; age 15.89±1.54 years; height 163.11±6.19 cm; weight 55.33±5.07 Kg) and a training group (TG; n = 9; age 16.11±2.47 years; height 161.56±5.25 cm; weight 57.56±8.11 Kg). Body shape, the performance of core stability, and landing kinetics were measured after 8 weeks of core stability training. Independent sample t-tests were used to compare baseline values between groups. A two-way repeated-measures analysis of variance (ANOVA) (time×group) was used. Results: The TG improved body shape, and waist circumference (t=-2.333, p=0.020). Performance of core stability, squat (t=-4.082, p=0.004), trunk flexion isometric test (t=-4.150, p=0.003), trunk lateral bending isometric test(t=-2.668, p=0.008), trunk rotation isometric test(t=-2.666, p=0.008), side bridge(t=-2.666, p=0.008), back hyperextension(t=-4.116,p=0.003), single foot triple jump(t=-4.184, p=0.003), and single-leg balance with eyes closed(t=4.167, p=0.003). Performance in landing kinetics, End /Phase (t=-4.015, p=0.004), sagittal axes (t=-4.598, p=0.002), frontal axis (t=3.116, p=0.014), peak power hip changing range (t=2.666, P=0.017), Peak power knee changing range (t=2.256, P=0.049). Conclusions: Core stability training leads to improvements in body shape, the performance of core stability, and landing kinetics. Therefore, these improvements can improve the sporting performance in Freestyle skiing aerials competitions.